Brain tumor diagnosis with MRS: The single voxel INTERPRET Decision-Support System version 2.0 - Olier, I.; Julià-Sapé, Margarida; Candiota, Ana Paula; Arús, C.; Pérez Ruiz, Alexander (Springer, 2008)
A medical off-line decision support system (DSS) for helping in the diagnosis and grading of brain tumours was developed in the frame of a multicentric European project [1] and has been further developed up to version 2.0 since 2003. This system is based on the analysis of SV-derived MRS data from 1.5 T MRI scanners. The current 2.0 version has the following new features with respect to the initial version: - Capability for entering SV RAW DATA for testing new cases from the following manufactures: Philips, Siemens "raw" and GE up to version 9x (using shf header file). - Capability for entering jMRUI-processed spectra. - Retrained classifier for short TE. - Classifier for long TE, for the following superclasses: low-grade meaningioma, low-grade glial and high-grade aggresive (glioblastomas and metastases). - Capability for making personalised overviews at Long TE in addition to the already avialable short TE.

En el marco de un proyecto europeo multicéntrico [1] se desarrolló un sistema médico de apoyo a la toma de decisiones (DSS) fuera de línea para ayudar en el diagnóstico y la clasificación de tumores cerebrales, que se ha seguido desarrollando hasta la versión 2.0 desde 2003. Este sistema se basa en el análisis de datos de MRS derivados de SV a partir de escáneres de RM de 1,5 T. La actual versión 2.0 presenta las siguientes novedades con respecto a la versión inicial: - Capacidad para introducir DATOS SV RAW para probar nuevos casos de los siguientes fabricantes: Philips, Siemens "raw" y GE hasta la versión 9x (utilizando el fichero de cabecera shf). - Capacidad para introducir espectros procesados por jMRUI. - Clasificador reentrenado para TE corto. - Clasificador para TE largo, para las siguientes superclases: meaningioma de bajo grado, glial de bajo grado y agresivo de alto grado (glioblastomas y metástasis). - Posibilidad de realizar resúmenes personalizados de los TE largos, además de los TE cortos ya disponibles.